100 Jahre Federal Reserve System - Weber, Christoph; Wölfel, Katrin (Wirtschaftsdienst, 2013)

Anspruchslöhne: immer noch Unterschiede zwischen Ost und West - Weber, Christoph; Dees, Philipp (WSI-Mitteilungen, 2015)
Die immer noch bestehenden Lohnunterschiede zwischen Ost- und Westdeutschland werden häufig kontrovers diskutiert. Oft werden dabei als Erklärung Unterschiede in der Arbeitsmarktsituation oder bei der Produktivität herangezogen. Die Unterschiede könnten aber auch daraus resultieren, dass in Ostdeutschland von Arbeitsuchenden niedrigere Löhne erwartet werden als im Westen. In diesem Zusammenhang diskutiert der folgende Aufsatz, ob eine Differenz in den Lohnerwartungen zwischen Ost- und Westdeutschen auch bei Berücksichtigung anderer Einflussfaktoren besteht. Dass dies tatsächlich der Fall ist – wie die Ergebnisse zeigen –, stellt eine Herausforderung für die Lohn- und Tarifpolitik dar, wenn eine Angleichung der Löhne zwischen Ost- und Westdeutschland angestrebt wird.
Keywords: Arbeitsmarkt; Anspruchslöhne; Lohnpolitik; Ostdeutschland; Westdeutschland

Central Bank Transparency and Inflation (Volatility) – New Evidence - Weber, Christoph (International Economics and Economic Policy, 2018)
Keywords: Central Bank Transparency; Inflation; Inflation Volatility; Determinants of Inflation; Central Bank Independence

Determinants of Risk Tolerance - Weber, Christoph (International Journal of Economics, Finance and Management Sciences, 2014)

Deutsche Leistungsbilanzüberschüsse in der Kritik - Weber, Christoph; Wölfel, Katrin (Wirtschaftsdienst, 2014)

ECB: Credibility at Risk? - Weber, Christoph (Applied Economics Quarterly, 2014)

ECB: Independence at Risk? - Weber, Christoph; Forschner, Benedikt (Inter economics, 2014)

EZB: Mehr Transparenz - Weber, Christoph (Wirtschaftsdienst, 2013)

EZB: Mehr Transparenz wagen - Weber, Christoph (Wirtschaftsdienst, 2012)

La Euro crisis. Causas y síntomas - Weber, Christoph (Estudios Fronterizos, 2015)

Makroökonomische Auswirkungen des demografischen Wandels - Weber, Christoph; Dees, Philipp (Das Wirtschaftsstudium, 2013)

Mikroökonomische Auswirkungen einer Umfinanzierung der Sozialversicherungen - Dees, Philipp; Weber, Christoph (Wirtschaftswissenschaftliches Studium, 2013)
Das deutsche Sozialsystem gilt als lohnzentriert. Damit ist gemeint, dass zur Finanzierung der Sozialleistungen Beiträge auf die Lohneinkommen erhoben werden. Dies verteuert den Arbeits- gegenüber dem Kapitaleinsatz. Zudem reduziert dies das Arbeitsangebot. Als Alternative bietet sich eine Umfinanzierung auf direkte Steuern oder Pauschalbeiträge an. Der vorliegende Beitrag analysiert mithilfe eines neoklassischen Arbeitsmarktmodells, wie sich die unterschiedlichen Finanzierungsalternativen auf Arbeitsangebot und Arbeitsnachfrage auswirken.
Keywords: Sozialpolitik; Sozialversicherungen; Arbeitsmarkt; Mikroökonomie

More on Calendar Effects on Islamic Stock Markets - Weber, Christoph; Nickol, Philipp (Review of Middle East Economics and Finance, 2016)
There is a long tradition in detecting anomalies of the Efficient Market Hypothesis. Among these are calendar anomalies, first described by French back in 1980. Whilst there is a plethora of studies for well-developed stock markets, there is still a lack of comprehensive studies for some small or emerging financial markets. It is particularly interesting to test not only for calendar effects in the conventional Gregorian calendar but also in other calendars like the Hijri calendar. Thus, the aim of this study is to provide a comprehensive analysis of calendar anomalies on Islamic stock markets. Firstly, we deliver a complete literature review of previous studies dealing with calendar effects on Islamic stock markets showing that there is still a lack of consensus about the effects. Secondly, we analyse whether there are any seasonal patterns in stock markets’ returns by conventional estimation techniques. Thirdly, we study whether those calendar effects are still apparent when we control for volatility clustering. In fact, there is evidence for calendar anomalies on all stock markets. However, those effects are prone to changes when different models or distributions are used. One should, therefore, be careful when interpreting calendar effects on Islamic stock markets. The evidence for theories put forward when analysing Western stock markets is – at best – mild.
Keywords: Islamic stock markets; calendar anomalies; day-of-the-week-effect; Ramadan effect; volatility

Searching for the Fed’s reaction function - Wölfel, Katrin; Weber, Christoph (Empirical Economics, 2017)
There is still some doubt about those economic variables that really matter for the Fed’s decisions. In comparison with other estimations, this study uses the approach of Bayesian model averaging (BMA). The estimations show that over the long-run inflation, unemployment rates and long-term interest rates are the crucial variables in explaining the Federal Funds Rate. In the other two estimation samples, also the fiscal deficit and monetary aggregates were of relevance. There is also evidence for interest rate smoothing. In addition, we account for parameter instability by combining BMA with time-varying coefficient (TVC) modelling. We find strong evidence for structural breaks. Finally, a model average is constructed via an TVC-BMA approach.
Keywords: Fed; Monetary policy reaction functions; Model uncertainty; Bayesian model averaging; Parameter instability

The effect of central bank transparency on exchange rate volatility - Weber, Christoph (Journal of International Money and Finance, 2019)

The Euro crisis. Causes and symptoms - Weber, Christoph (Estudios Fronterizos, 2015)

The Iraqi Stock Market: Development and Determinants - Kähler, Jürgen; Weber, Christoph; Haider, Salahal-Din Aref (Review of Middle East Economics and Finance, 2014)

Theorien der Entscheidung unter Unsicherheit - Kähler, Jürgen; Weber, Christoph (Wirtschaftswissenschaftliches Studium, 2015)

The unemployment effect of central bank transparency - Weber, Christoph (Empirical Economics, 2019)

Zentralbank: Deutsche Bankenaufsicht bündeln - Kähler, Jürgen; Weber, Christoph (Wirtschaftsdienst, 2013)